RETRACTED: Efficiency of grazing for adult culled sheep in the southern regions of Kyrgyzstan - Orozbaev Bolotbek; Chortanbaev Tyrgoot; Turdubaev Taalaibek; Bekturov Amantur; Kadyrova Chinara (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 116, 00001 (2024), https://doi.org/10.1051/bioconf/202411600001